2016
DOI: 10.5812/ircmj.31314
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Extract Supplementation and the Effects on the Biomarkers of Oxidative Stress and Metabolic Profiles in Female Volleyball Players: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: BackgroundOnly limited data are available for evaluating the effects of the administration of grape seed extract (GSE) on the metabolic status of female volleyball players.ObjectivesThis study was conducted to determine the effects of GSE administration on the metabolic status of female volleyball players.MethodsThis randomized, double-blind, placebo-controlled clinical trial was performed among 40 female volleyball players. The subjects were randomly divided into two groups, with members of the test group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 31 publications
0
63
0
1
Order By: Relevance
“…After screening 724 studies, 15 (Abedini et al, ; Alirezaei et al, ; Argani et al, ; Clifton, ; Kar, Laight, Rooprai, Shaw, & Cummings, ; Mellen, Daniel, Brosnihan, Hansen, & Herrington, ; Park, Edirisinghe, Choy, Waterhouse, & Burton‐Freeman, ; Pourghassem‐Gargari, Abedini, Babaei, Aliasgarzadeh, & Pourabdollahi, ; Sano et al, ; Sivaprakasapillai, Edirisinghe, Randolph, Steinberg, & Kappagoda, ; Taghizadeh, Malekian, Memarzadeh, Mohammadi, & Asemi, ; Terauchi et al, ; Turki et al, ; Vigna et al, ; Ward et al, ) of them were eligible to be included in this meta‐analysis. These studies were detected by a process that is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening 724 studies, 15 (Abedini et al, ; Alirezaei et al, ; Argani et al, ; Clifton, ; Kar, Laight, Rooprai, Shaw, & Cummings, ; Mellen, Daniel, Brosnihan, Hansen, & Herrington, ; Park, Edirisinghe, Choy, Waterhouse, & Burton‐Freeman, ; Pourghassem‐Gargari, Abedini, Babaei, Aliasgarzadeh, & Pourabdollahi, ; Sano et al, ; Sivaprakasapillai, Edirisinghe, Randolph, Steinberg, & Kappagoda, ; Taghizadeh, Malekian, Memarzadeh, Mohammadi, & Asemi, ; Terauchi et al, ; Turki et al, ; Vigna et al, ; Ward et al, ) of them were eligible to be included in this meta‐analysis. These studies were detected by a process that is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…General characteristics of eligible studies are summarized in Table . The studies were conducted in Italy (Vigna et al, ), Australia (Clifton, ; Ward et al, ), Japan (Sano et al, ; Terauchi et al, ), United Kingdom (Kar et al, ), United States (Mellen et al, ; Park et al, ; Sivaprakasapillai et al, ), Iran (Abedini et al, ; Alirezaei et al, ; Argani et al, ; Pourghassem‐Gargari et al, ; Taghizadeh et al, ), and Tunisia (Turki et al, ). Studies were published between 2003 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…De fato, um elevado estresse oxidativo tem sido encontrado em atletas de combate 32,33 . Estes dados devem ser ponderados pelo fato de que a MDA é um metabólico inespecífico para avaliação do estresse oxidativo 34 , embora venha sendo usada em estudos que avaliam este fenômeno 35,36 . Quanto à PCR-us, um resultado semelhante ao do presente estudo foi observado por Garatachea et al 37 , em oito atletas de caiaque durante 42 semanas de treinamento.…”
Section: Discussionunclassified